Penerapan Model Problem Based Learning (PBL) Berbantuan Video Pembelajaran dan Quizizz Untuk Meningkatkan Hasil Belajar Siswa - Pramasanti, Desak Ketut; Kundera, I Nengah (Jayapangus Press, 2025)
By implementing an effective learning model and packaging it using interesting technological media, it is also hoped that it will be able to improve student learning outcomes. As for the aim of this research is to determine the application of the model Problem Based Learning (PBL) assisted by learning videos and Quizizz to improve student learning outcomes. This research is classroom action research using test and observation methods. The subjects of this research were 25 students of class VII G of SMP Negeri 6 Kintamani. Data collection was carried out using test and observation methods during learning activities. The research results show that it was found that there was a significant increase in the average score of students' mathematics learning outcomes. Initially in the first cycle the average student score was 66,8 which is categorized as poor in Cycle I, to 77.2 in Cycle II which is already in the good category with an increase of 10.4. Furthermore, there were 60% of students who scored above the Learning Goal Achievement Criteria (KKTP) in Cycle I and 84% of students in Cycle II with an increase of 24%. Thus, student learning outcomes have improved by using the learning model Problem Based Learning (PBL) assisted by learning videos and Quizizz.